2013
DOI: 10.1097/jnr.0b013e3182921ff6
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Widowhood, Chronic Disease, and Physical Function on Mortality Among Older People

Abstract: The study confirmed that widowhood, chronic disease, and physical function were strongly associated with mortality hazard in older people. Therefore, greater attention should be paid to these factors to reduce elderly mortality risk. Research results should be useful in developing welfare strategies for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(45 reference statements)
0
8
0
1
Order By: Relevance
“… a BADL Basic Activities of Daily Living b Based on International Classification of Diseases -10th version and categories used in previous studies, chronic diseases identified in present study included hypertension, stroke, diabetes, heart disease, bronchitis, pneumonia, tumor, et al [40, 41]…”
Section: Resultsmentioning
confidence: 99%
“… a BADL Basic Activities of Daily Living b Based on International Classification of Diseases -10th version and categories used in previous studies, chronic diseases identified in present study included hypertension, stroke, diabetes, heart disease, bronchitis, pneumonia, tumor, et al [40, 41]…”
Section: Resultsmentioning
confidence: 99%
“…Older adults with chronic illnesses exhibited a higher risk of falls (Sibley, Voth, Munce, Straus, & Jaglal, 2014) and were more likely to experience a deterioration in multiple organs or systemic functions leading to physical dysfunctions or disabilities (Lu, Chen, Tang, & Tung, 2014). Chronic illnesses may also increase the risk of death (Ho & Hung, 2013). These factors may lead to poor performance in the activities needed for daily living or to psychological stress for the older adults, resulting in an increased burden of care for family members.…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed that in general, the widowed had excess mortality (compared with marriage), around 15% 3 months after the death of spouses [11]. In Taiwan, a previous study found that between 1999 and 2007, the widowed were 1.2 times more likely to die prematurely than married persons [8], and there were significant differences in gender and socioeconomic, mental, and physical status between widowed and nonwidowed persons [13][14][15]. The literature showed that the possible factors for the high risk of death in the widowed include physical and mental health, lifestyle, social support, and economic status [7,11,14,15].…”
Section: Introductionmentioning
confidence: 99%